An autocatalytic CO hydrogenation approach for the fabrication of stable Fe-based superhydrophobic surfaces. Issue 62 (14th July 2022) - Xue, Yingying; Duan, Shengyang; Liu, Zihao; Cui, Miaomiao; Xiong, Zhanghui; Liu, Zengchen; Chen, Jiangang
Abstract : Hydrocarbons were constructed in situ on a rough surface via an autocatalytic CO hydrogenation reaction to prepare superhydrophobic materials. Abstract : Stable Fe-based superhydrophobic surfaces are constructed via a hydrothermal method and an autocatalytic CO hydrogenation reaction. The platform molecule of syngas is proposed as an alternative to traditional low-free-energy materials. Syngas may be a powerful tool for fabricating superhydrophobic surfaces that can catalyze the CO hydrogenation reaction.